Participative Interaction Between Specialists and Parents in Early Intervention During the War in Ukraine - Hanna Kukuruza; Olena Bliznyuk; Serhiy Tsylyuryk (Вісник Харківського національного університету імені В.Н. Каразіна. Серія: Психологія)
The article examines the life and professional situation in which early intervention specialists found themselves at the beginning of the war in Ukraine, their needs and features of providing early intervention services to families during wartime. A model of participatory interaction between specialists and the family in early intervention was also built, on the basis of which the checklist "Implementation of early intervention family plan: meeting with the family" was created. Questionnaire and modeling methods were used. Specialists from Kharkiv, Zakarpattia, Odesa, Lviv, Donetsk, Luhansk regions and Vinnytsia were involved (N=76). 52.6% of the surveyed specialists were forced to change their place of residence after leaving the territory of active hostilities. Among those who left, 17.1% of specialists were abroad. 81.6% of specialists continued to work, of which 74.19% - provided RV service, despite the war and forced resettlement. The results of the questionnaire became the basis for creating a model of participatory interaction and its operationalization in the form of a checklist, which consists of five sections that reflect the sequence of actions of specialists: transdisciplinary team, preparation for a meeting with the family, greetings, implementation of goals and support of parents, summarizing and planning the next meeting .The developed checklist is based on evidence-based practices of early intervention and allows to ensure the measurability of participative interaction, which ensures the quality of meetings during the implementation of the family plan of early intervention and their compliance with recommended practices. In the conclusions, the structure of the needs of emergency personnel during the war in Ukraine was determined: obtaining new knowledge about accompanying families and children during the war, knowledge about trauma and work with it, communication with colleagues, financial and material needs, the need for emotional support to prevent emotional burnout; the checklist "Implementation of  early intervention family plan: meeting with the family" was substantiated and developed, which allows operationalizing the concept of participatory interaction in early intervention.